Semantics - Saeed, John I. (Introducing linguistics, 2023)
"This fifth edition of Semantics has been thoroughly revised and updated to reflect the most recent theoretical developments in the field of linguistic semantics. Divided into three parts, Semantics provides and engaging introduction to the field for students new to the field by establishing the place of semantics within linguistics, introducing key topics in the description of word and sentence meaning, and reviewing the main current theoretical approaches to semantics. A significant update to this edition is an entirely new chapter introducing the incursion of pragmatics into traditional areas of semantics including that of Recanati, Relevance Theory and truth-conditional meaning. This new chapter will offer students a clear understanding of the overlap between the subdisciplines. Key pedagogical features through every chapter will be updated such as the exercises with solutions which are designed to further knowledge of linguistic concepts, and a helpful glossary of technical terminology will remain. Semantics, 5th Edition, continues to set the standard as the most invaluable and accessible introduction to the field of contemporary linguistic semantics available today"-- Provided by publisher.